Microbial electrosynthesis for wastewater treatment: principles, process and performance - Yeo, Sherlyn Mei Shan (Nanyang Technological University, 2022)
Global warming is a major issue in the world today. Wastewater treatment plants is one of the sources of carbon dioxide emission. Several technologies have been invented to curb the carbon dioxide emission into the atmosphere. One such technology is microbial electrosynthesis which use organic carbon in wastewater as a substrate for the bacteria in the anode chamber. The bacteria oxidises the organic carbon, releasing carbon dioxide, electrons and protons. The electrons travel through the external circuit into the cathode chamber while the carbon dioxide and protons pass through a membrane. Another type of bacteria in the cathode chamber than utilize the carbon dioxide and electrons to form valuable organic compounds, hydrogen gas and met. MES technology could have different reactor configurations and each has its own advantages and disadvantages. One such configuration utilizes reverse electrodialysis stack in place of a membrane. This report analyzed the performance of MES technology using reverse electrodialysis stack (microbial reverse electrodialysis cell) and it was found to have a total organic carbon removal efficiency that is similar to a conventional wastewater treatment plant (~86%). In addition, energy consumption of a microbial reverse electrodialysis cell is low due to the use of thermolytic solution to drive the elections across the external circuit. Through the comparison between conventional wastewater treatment plant and MES technology, it was concluded that MES technology should be incorporated into conventional wastewater treatment plants since there is no significant decrease in TOC removal efficiency and the energy consumption by MES technology is much lower than that of conventional wastewater treatment plant.